THE ROLE OF HUMAN CAPITALIN ENSURING EFFECTIVE DEVELOPMENT OF ENTERPRISES - BOIKIVSKA, Galyna; SALADIAK, Kseniia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the role of human capital in the production and economic activity of the enterprise. It was determined that the most important condition for increasing the competitiveness of a modern enterprise is the formation of highly developed human capital capable of producing not only new knowledge, but also competitive advantages in any sphere of activity. One of the main directions of the development of personnel of enterprises is the organization of interrelated processes of development of competitive and personal abilities of an employee. The experience of many foreign companies indicates the strengthening of the role of human resources management in the system of factors that ensure competitiveness. In order to achieve a more stable competitive position, the enterprise must constantly develop personnel development programs that would ensure the satisfaction of many needs of employees, development and improvement of professional and general educational level. Sufficient provision of enterprises with human capital of the appropriate level of qualification and professional skills, its rational use, high level of labor productivity are of great importance for increasing production volumes and improving production efficiency.Human capital forms 70% of the national wealth of developed countries and only 30% of the national wealth of Ukraine. It is even worse that while developed countries are increasing their human capital, Ukraine is losing it: demographic and migration losses, the mismatch of education and qualifications of workers with the requirements of the times, low labor productivity and innovativeness of the economy, the full-scale invasion of Russia on the territory of Ukraine are leading us to disaster. Extremely low labor productivity in Ukraine will continue to decline, as a large number of the population is currently out of work, leaving the country, many enterprises are suspending their work and reducing their staff. Determining the main causes of existing problems and creating an effective strategy for the restoration of human capital is the main condition for the revival of Ukraine after the war.Enterprises today must become socially active and be included in processes of a nationwide nature, cooperating with civil organizations and, what is especially important in today's conditions, the volunteer movement. It is obvious that every enterprise has people who are directly or indirectly involved in the mobilization processes, volunteering, charity, who may have suffered losses due to the war, therefore the management of the enterprise has no right to be indifferent to the fate of its team. By forming corporate volunteering, enterprises join general processes, demonstrating their social importance, social responsibility and increasing their image on the market. National consciousness is a component of human capital. It was thanks to the level of patriotic intelligence that there was a rallying of the population of Ukraine, the creation of volunteer aid centers, provision of the Armed Forces and territorial aid with charitable contributions to support their activities. In general, the biophysical, intellectual and social components of human capital give an awareness of the importance of the work of individuals and their contribution to the functioning of the economy in wartime.
Keywords: human capital; development; competitiveness; economic growth; productivity